Success of reformulation and health education in reducing sodium intakes across socioeconomic groups. (30th September 2020) - Gressier, M; Frost, G; Sassi, F
Abstract: Background: The UK salt reduction programme started in 2005, consisting of education campaigns and a reformulation strategy. This programme is often cited as an example of a successful public health programme, and used as a model for other programmes. This study aims at assessing how the programme succeeded in reducing sodium intakes, and whether success was even across socioeconomic (SES) groups. Methods: Food intakes for the UK adult population were derived from food diaries in the UK National Diet and Nutrition Survey for 2008/09 (Y1) and 2016/17 (Y9). Year-specific sodium densities of foods were used to calculate the quantity-weighted average sodium density of all food and beverage consumed by the population. Using a decomposition approach (Griffith et al., Economica, 2017), changes in sodium density were attributed to either changes in food composition (change in sodium density), or changes in behaviour (type and quantity of food products consumed), stratifying by SES. Results: The programme was linked to a 16% decrease in sodium intakes between Y1 and Y9, while sodium density decreased by 15%. This decrease was largely driven by reformulation (-12mg/100g), while changes in food choices had a smaller impact (-2mg/100g). This finding was consistent across SES groups, whether stratified by education or income, with no significant differences between SES groups in behavioural responses to the programme (changes in food choices). Conclusions: Changing people's food environment, through reformulation to reduce the sodium density of foods, had a larger impact on sodium intakes in the UK population than efforts to change food choices, and produced consistent impacts across SES groups. Key messages: Reformulation led to a consistent reduction of the sodium density of food consumed across SES. There was no evidence of adverse equity impact from changes in behaviour.